Soil quality enhancement drives tree growth and broadleaf dominance in fir-broadleaf mixed plantations - Fu, Zhigao; Xiao, Yihua; Liu, Shirong; Xu, Han; Wang, Yan; Zhu, Huosheng (Frontiers in Plant Science, 2025)
IntroductionEvaluating soil quality is essential for guiding reforestation and land management strategies, particularly in degraded Chinese fir plantations where long-term productivity and successional dynamics remain poorly understood.MethodsThis study assessed ten mixed-species planting patterns to quantify the Soil Quality Index (SQI) using a Minimum Data Set (MDS) approach, which reduces data redundancy by statistically identifying key indicators from a larger dataset, thereby effectively capturing essential soil functions, and subsequently explored the relationships between SQI and stand growth, structural diversity, biomass, net primary productivity (NPP), as well as percentage of broadleaf species (PBS).ResultsSignificant differences were observed across planting patterns in diameter at breast height (DBH), tree height (TH), stand biomass (FB), structural diversity (variation in DBH [CVD] and Gini coefficient [GiniD]), and PBS. Soil properties—including physical (soil moisture), chemical (soil organic carbon [SOC], total nitrogen [TN], total phosphorus [TP], ammonium nitrogen [NH₄⁺], nitrate nitrogen [NO₃⁻], available phosphorus [AP]), microbial (microbial biomass carbon [MBC], nitrogen [MBN], and phosphorus [MBP]), and enzymatic (e.g., peroxidase [POD], alkaline phosphatase [ALP], urease [URE])—also varied significantly. SQI values ranged from 0.42 to 0.65, with patterns Fir–Mytilaria laosensis mixed (ML), Fir–Castanopsis hystrix mixed (CH), Fir–Michelia chapensis mixed (MC), and Fir–Schima superba mixed (SS) associated with both high SQI and greater biomass. Sensitivity analysis identified Fir–Cinnamomum porrectum mixed (CP), ML, and SS as particularly responsive to hybridization. Among soil factors, URE, AP, and MBC were key drivers of productivity, while URE, AP, MBC, and POD significantly predicted the proportion of broadleaf trees. Enhanced soil quality was positively associated with increases in DBH, TH, and PBS, accelerating the successional transition from fir-dominated to broadleaf-dominated stands. However, SQI was not significantly correlated with structural diversity metrics.DiscussionThese results underscore the importance of rational species selection in restoring degraded fir plantations and demonstrate that improving soil quality is a critical mechanism promoting near-natural forest succession.